Jewish exegesis and Homeric scholarship in Alexandria - Niehoff, Maren R. (Cambridge Univ. Press, 2011)
"Systematically reading Jewish exegesis in light of Homeric scholarship, this book argues that more than 2000 years ago Alexandrian Jews developed critical and literary methods of Bible interpretation which are still extremely relevant today. Maren Niehoff provides a detailed analysis of Alexandrian Bible interpretation, from the second century BCE through newly discovered fragments to the exegetical work done by Philo. Niehoff shows that Alexandrian Jews responded in a great variety of ways to the Homeric scholarship developed at the Museum. Some Jewish scholars used the methods of their Greek colleagues to investigate whether their Scripture contained myths shared by other nations, while others insisted that significant differences existed between Judaism and other cultures. This book is vital for any student of ancient Judaism, early Christianity and Hellenistic culture"--